Pengembangan E-Modul IPS Berbasis Literasi dan Perubahan Sosial Budaya pada Masa Pandemi Covid-19 - Tejokusumo, Bambang; Shalihati, Sakinah Fathrunnadi (Jurnal Didaktika Pendidikan Dasar, 2022)
The purpose of this research is to produce social studies e-modules based on literacy and socio-cultural changes during the Covid 19 pandemic. The background for developing e-modules is the lack of learning media used independently by students when learning online. The development method used is the Research & Development Method from Borg, W.R & Gall. This method is modified according to need into seven stages. The research subject is e-module which is tested from material, language and graphic elements by experts, teachers and students. The test results obtained a score of 81.7 (good, needs partial revision), 91.6 (very good, does not need revision), and 91.9 (very good, does not need revision). The average score is 88.4 (very good), which means that it is worthy of being used as reading material if it refers to bookkeeping standards. Improvements are still made based on input during the trial, before being widely disseminated and implemented. The resulting e-module has limitations that need to be developed further, especially on the themes or backgrounds studied in social studies subjects.